Analysis of RELAP5 prediction of countercurrent flow limitation in downcomer at upper plenum test facility. (April 2023) - Li, Xiang; Sun, Wan; Ding, Shuhua; Huang, Tao; Ma, Zaiyong; Zhang, Luteng; Zhu, Longxiang; Pan, Liang-ming
Abstract: The relevance of the countercurrent flow limitation phenomenon is known in nuclear (emergency core cooling and accident situations) industries, such as a Loss of Coolant Accident (LOCA). The occurrence of countercurrent flow limitation (CCFL), which can exist in a host of places around the nuclear reactor system, will prevent the emergency cooling water, which is necessary to cool the core successfully flowing into the core from the downcomer of Pressurized Water Reactor (PWR) in the LOCA. Accurate prediction of the downcomer CCFL phenomenon is significant for the design and analysis of reactor safety. Among the experiments at Upper Plenum Test Facility (UPTF), various tests, test 6 and test 7 are studied in this research. Those tests are conservatively evaluated to predict the CCFL phenomenon at the downcomer. Above all, the methodology of node partition used in the RELAP5 model for the channels with cross-connections to represent the circumferential downcomer annulus was also studied. In particular, the nodes along the circumferential direction had a vital effect on the prediction of the steam velocity profile of downcomers. The influence of the CCFL model, including the most widely used Wallis-type and Kutateladze-type correlations, and the cooling-limited liquid-downflow behavior were analyzed. In addition, the pressure on the downcomer and steam flow rate of the break were monitored, and the predicted results were also analyzed.